Distribution, Behavioral Ecology and Present Status of Varanus flavescens (a literature review paper) in Nepal - Karki, Ajay; Bista, Rabindra; Humagain, Santosh (The Initiation, 2010)
Golden monitor lizard is a reptilian with long slender body, long neck, flexible head movable in all directions, feature that is not possessed by any other reptile. It is protected on international scale; listed in CITES appendix 1, the IUCN red data list, and categorized as protected reptile under national park and wildlife conservation act of Nepal. Even if distribution is wide it is threatened to extinction in much of its inhabitant range because of habitat destruction along with hunting for its hides, exploited for food and skin values. Exported illegally through northern Nepal to china as its skin is used in traditional Chinese medicine. To maintain their number as of this circumstances; habitat conservation and civic consciousness from stakeholders in integrated mode to minimize hunting, possibly will be the plausible way. This carnivore reptile is oviparous can grow up to 90 cm in length and tail measures about 49 cm. Becomes sometimes dangerous, if threatened, rises high on its legs , hisses loudly, sways its body and lashes its razor like sharp tail and ready to cut offender and defend itself. So this paper reveals with distribution, ecological behavior and present status on Golden Monitor Lizard in Nepal. Key Words: Protected, Threatened, Oviparous, Carnivorous, Medicine, Juveniles DOI: 10.3126/init.v2i1.2523 The Initiation Vol.2(1) 2008 pp49-54